THE IMPORTANCE OF USING PEDAGOGICAL SOFTWARE TOOLS IN SCHOOL EDUCATION - Davranova Gulbahor Numondjonovna (Zeta Repository, 2023)
Today, the emergence of multimedia and Internet technologies has opened a wide way for the use of information technology as an effective tool in the processes of education and education, communication of secondary schools. Abstract: Today, the emergence of multimedia and Internet technologies has opened a wide way for the use of information technologies as an effective tool in education and training, communication processes in general education schools. In this article, the increasing role and influence of information technologies in the development of a well-rounded person, his independent choice of profession and professional self-formation, professional skill development, the use of computer programs in classes, the shift of focus from reproductive activities to creative activities, enriching learning, enabling the development of associative and emotional memory and audiovisual perception, especially activating the learning process and providing students with a comfortable learning environment are highlighted.